DINAMIKA BUDAYA DAN SOSIAL DALAM PERADABAN MASYARAKAT SUNDA DILIHAT DARI PERSPEKTIF SEJARAH - Yat Rospia Brata; Yeni Wijayanti (Universitas Galuh, 2020)
The present study aims to uncover the historical development of Sundanese people’s local entities of cultural and social dynamics from the old and recent frame and its relationship with current trends of “life” digitalization. Local wisdom growing in Sundanese social structure reflects its cultural and social identities of people as each time period indicates. Culturally, life constructs of Sundanese people refers to the Kagaluhan values that promote high civilization as reflected from arts, musical, and local traditional performances such as dances and puppets, which suggest uniquely genuine local identities. Socially, the Sundanese’s people ways of Socializing process proved egalite. The study include steps of data collection through analyzing historical sites, artefacts, and documents, and interpreting them with reference to the civilization process of each time. Moreover, the analysis of both dynamics is also encountered by the reality of current trend of disruption of digital era. The study shows that Sundanese people’cultural and social constructs represent high quality of meaningful life.Penelitian ini bertujuan untuk mengungkap perkembangan sejarah budaya dari entitas lokal masyarakat Sunda dan dinamika sosial budaya dari sudut pandang masa lampau dan masa kini serta hubungannya dengan tren saat ini yaitu digitalisasi